Yucca aloifolia seed oil: a new source of bioactive compounds - Mokbli, Sadok; Nehdi, Imededdine Arbi; Sbihi, Hassen Mohamed; Chin, Ping Tan; Al‑Resayes, Saud Ibrahim; Rashid, Umer (Springer, 2018)
Yucca aloifolia Linn (Y. aloifolia), also known as Spanish bayonet, is a drought-tolerant plant containing important bioactive compounds in various parts of the plant. Y. aloifolia is used as a natural medicinal herb. The purpose of the present study was to characterize and evaluate the seed oil extracted from Y. aloifolia seeds. The oil content of the seeds was 16.23%. The principal fatty acids in the oil were linoleic acid (73.38%), oleic acid (13.52%) and palmitic acid (8.18%). The oil has high vitamin E activity because of an appreciable concentration of tocols (204 mg/100 g), particularly tocotrienols, which represent 79% of the total amount of tocols. Tocotrienols have powerful antioxidant, anticancer, neuro/cardio protective and cholesterol-lowering properties. The thermal profile of Y. aloifolia seed oil was examined differential scanning calorimetry (DSC). Y. aloifolia seed oil is considered to be healthy dietary oil.